Dynamic Valuation Modelling of Cost and Electricity Consumption Over Local Objects with Intellectual Governance - Osypenko, V.V.; Kaplun, V.V.; Voronenko, M.O. (Control systems & computers, 2020)
The work is devoted to the further development of the theory of intelligent electric power management systems construction for local objects with several heterogeneous (traditional and renewable) energy sources. The scientific idea is based on the use of modern information systems and technologies and is to improve the energy efficiency of the micro-energy networks of local objects based on the dynamic estimation of the real-time electricity cost and the transmission of this information to the user with the agreed discretion for matching the load schedule (or demand schedule). The method of dynamic planning of energy use in micro-energy systems and principles of building intelligent energy management systems of local objects are developed, on the basis of which the user will be able to control the load levels in real-time and optimize the energy costs, which in turn will lead to balancing of the microelectric network and increase the efficiency of its functioning. It is proved that the proposed solutions for the formation of control and technological functions can be used to improve the intelligent control systems in technologies smart microgrid, smart house, etc.